Primary thyroid squamous cell carcinoma with severe respiratory stenosis and endotracheal invasion: a case report with literature review - Xueliang Liu; Shang Ma; Yuxin Zheng; Zeming Xu; Hui Hao; Hongyan Ma; Qian Xu (Frontiers in Medicine)
IntroductionPrimary squamous cell carcinoma of the thyroid (PSCCT) is a rare and highly aggressive malignant tumor with a poor prognosis. Although surgery, chemotherapy and other treatment methods have been reported, the current treatment modality has not reached a consensus. This study discusses the diagnosis and treatment of a case of PSCCT with severe respiratory stenosis and endotracheal invasion and reviews the relevant literature. We report the disease of rapidly enlarging mass leading to asphyxiation to raise clinicians’ awareness of this condition.Case presentationWe report a 76-year-old woman presenting with an enlarging right thyroid mass accompanied by severe dyspnea and hoarseness. Computed tomography (CT) scan disclosed a large solid heterogenous nodule with calcification in the right thyroid lobe and prominent adjacent lymph nodes. PSCCT was confirmed by postoperative histopathology and immunohistochemistry. Thyroidectomy with partial tracheectomy and tracheostomy was performed to relieve the patient’s dyspnea. The patient has been discharged after receiving post-operative supportive care.ConclusionClinicians should pay attention to the rapidly enlarging neck mass as it may cause asphyxiation and avoid the loss of treatment opportunities.